Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s10194-011-0405-6
|View full text |Cite
|
Sign up to set email alerts
|

Antimigraine medication use and associated health care costs in employed patients

Abstract: Migraine is under diagnosed and suboptimally treated in the majority of patients, and also associated with decreased productivity in employees. The objective of this retrospective study is to assess the antimigraine medication use and associated resource utilization in employed patients. Patients with primary diagnosis of migraine or receiving antimigraine prescription drugs were identified from an employer-sponsored health insurance plan in 2010. Medical utilization and health care costs were determined for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…In a recent study on the health care cost in the patients with migraine headache, it was suggested that 45% of the patients with migraine headache do not receive appropriate treatment. Total health care cost tends to be higher in these patients due to their frequent out-patient and emergency referrals compared to the ones receiving medications regularly, even expensive anti-migraine agents [15]. …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on the health care cost in the patients with migraine headache, it was suggested that 45% of the patients with migraine headache do not receive appropriate treatment. Total health care cost tends to be higher in these patients due to their frequent out-patient and emergency referrals compared to the ones receiving medications regularly, even expensive anti-migraine agents [15]. …”
Section: Discussionmentioning
confidence: 99%
“…More recently, another retrospective analysis of claims from an employer-sponsored health plan found that, after controlling for several covariates, migraine patients who used antimigraine medications had significantly lower migraine-related resource utilization compared with untreated migraine patients. 24 However, the analysis grouped together triptans, ergotamines, and NSAIDs as antimigraine medications. Furthermore, the analysis was entirely cross-sectional, and although regression models were used to control for several covariates, differences between treated and untreated migraine patients are likely to persist.…”
Section: Limitationsmentioning
confidence: 99%
“…Nevertheless, in clinical practice the use of these drugs is less widespread than that of other, less specific drugs, such as non-steroidal antiinflammatory drugs (NSAIDs). Several studies showed that among recognized migraineurs few subjects are submitted to specific treatment [5]. In a recent investigation, only from 0.7 to 1.0 % of the analyzed population on migraine subjects used triptans [6], while in other studies the percentage varied between 3.0 and 19 % [7,8].…”
Section: Introductionmentioning
confidence: 98%